2020
DOI: 10.3390/cancers12061372
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Sequencing of Tumor-Educated Platelets, a Novel Biomarker for Blood-Based Sarcoma Diagnostics

Abstract: Sarcoma is a heterogeneous group of rare malignancies arising from mesenchymal tissues. Recurrence rates are high and methods for early detection by blood-based biomarkers do not exist. Hence, development of blood-based liquid biopsies as disease recurrence monitoring biomarkers would be an important step forward. Recently, it has been shown that tumor-educated platelets (TEPs) harbor specific spliced ribonucleic acid(RNA)-profiles. These RNA-repertoires are potentially applicable for cancer diagnostics. We ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…Importantly, further development of the digitalSWARM algorithm as a tool to monitor GBM progression provided the demonstration that the TEP score represent tumor behavior and could be used to distinguish false positive progression from true progression (validation series, n = 20; accuracy, 85%; AUC, 0.86 [95% CI, 0.70-1.00; p < 0.012]). Although the initial analysis has provided promising proof-of-concept results, more samples should be included in future studies to make the prediction algorithm more robust, especially for the detection of false positive progression (Sol et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, further development of the digitalSWARM algorithm as a tool to monitor GBM progression provided the demonstration that the TEP score represent tumor behavior and could be used to distinguish false positive progression from true progression (validation series, n = 20; accuracy, 85%; AUC, 0.86 [95% CI, 0.70-1.00; p < 0.012]). Although the initial analysis has provided promising proof-of-concept results, more samples should be included in future studies to make the prediction algorithm more robust, especially for the detection of false positive progression (Sol et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…The PSO-enhanced diagnostic accuracy was 87% for the validation set (n = 53 samples, AUC of 0.93). Interestingly, the authors performed a Venn diagram analysis to access the uniqueness of the Sarcoma signature obtained, comparing it with previous studies in NSCLC (Best et al, 2017) and in LGG (Best et al, 2019), and concluded that a unique sarcoma signature can be selected from TEP RNA profiles (Heinhuis et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…Blood samples were obtained from the two University Hospitals of Amsterdam (VUmc and AMC, Amsterdam Universities Medical Centers (Amsterdam UMC, Amsterdam, The Netherlands), after receiving an informed consent of the patients (medical ethical approved protocol: #14438). Healthy donors were reported to be without any type of cancer, currently or in the past, as described previously [72]. The samples and associated clinical data of all individuals was collected and stored with a retraceable code, and fully anonymized.…”
Section: Patients and Samples Collectionmentioning
confidence: 99%
“…Research into the function of small extracellular vesicles (30~150nm) in the processes that potentiate local invasion [44], pre-metastatic niche formation [45], and immune system modulation [46] has provided insight into the distinguishing characteristics of tumour-associated exosomes that make them useful for liquid biopsies (reviewed in Zhou, B et al [20]). Platelets are 20-30 times larger than the largest exosomes and are capable of releasing exosomes of their own, and current research indicates tumours change the platelet RNA profile to a degree distinguishable from normal patients [19]; recent results for proof-of-concept screening in sarcoma patients indicate substantial differences compared to healthy donors and sarcoma patients in long-term remission [47].…”
Section: Introductionmentioning
confidence: 99%